The Investment Network, Sectoral Comovement, and the Changing U.S. Business Cycle - vom Lehn, Christian; Winberry, Thomas (Quarterly Journal of Economics, 2021)
Abstract We argue that the network of investment production and purchases across sectors is an important propagation mechanism for understanding business cycles. Empirically, we show that the majority of investment goods are produced by a few “investment hubs,” which are more cyclical than other sectors. We embed this investment network into a multisector business cycle model and show that sector-specific shocks to the investment hubs and their key suppliers have large effects on aggregate employment and drive down labor productivity. Quantitatively, we find that sector-specific shocks to hubs and their suppliers account for an increasing share of aggregate fluctuations over time, generating the declining cyclicality of labor productivity and other changes in business cycle patterns since the 1980s.